Pharmaceutical and Medical Devices Industry Regulation in Indonesia: Human Rights Perspective - Giannina Meracellene Lesmana; Matthew Darrell Tenando; Vienda Mustika Dewi (Jurist-Diction, 2022)
AbstractA deficiency in supply of medicines and medical devices, especially in remote areas, has become a national problem since the mid-2000s until now. This problem is certainly made worse by the presence of COVID-19. The main causes of this supply shortages are, among others, economic factors, ineffective regulations that result in problems related to business and supply chains. Indonesia, a country where 90% of raw materials for medicines are imported from abroad, of course is deeply affected by the export ban of countries that supply raw materials. Do not forget that Indonesia's geographical condition is so vast that it creates huge obstacles for the distribution of drugs and medical devices, and it is understandable if the private sector does not want to open hospitals, pharmacies or clinics in remote areas due to economic factors. As a result, human health, something which should be a human right feels like a luxury during this pandemic. Therefore several policies have been implemented, ranging from increasing production capacity, enacting regulations regarding limits on the number of drugs that can be prescribed to patients or purchased by the public to prevent hoarding, simplifying the industrial licensing process to increasing hospital beds.Keywords: Medical Devices; Medicine; COVID-19. AbstrakKurangnya pasokan obat dan alat kesehatan khususnya di daerah terpencil telah menjadi masalah nasional sejak pertengahan tahun 2000-an hingga saat ini. Masalah ini tentunya diperburuk oleh adanya COVID-19. Penyebab utama kekurangan pasokan ini diantara lain karena faktor ekonomi, regulasi yang kurang efektif yang mengakibatkan masalah terkait bisnis dan juga rantai pasok. Indonesia sebuah negara dimana 90% bahan baku obat obatan didatangkan dari luar negeri tentu sangat terpengaruh oleh larangan ekspor negara negara pemasok bahan baku. Tidak lupa kondisi geografis Indonesia yang begitu luas menghasilkan kendala yang begitu besar untuk distribusi obat dan alat medis, dan dapat dipahami jika pihak swasta tidak ingin membuka rumah sakit, apotek ataupun klinik di daerah terpencil karena faktor ekonomis. Lantas kesehatan yang seharusnya adalah Hak Asasi Manusia terasa seperti kemewahan di pandemi ini. Oleh sebab itu beberapa kebijakan yang dilakukan yaitu mulai dari meningkatkan kapasitas produksi, memberlakukan peraturan mengenai batasan jumlah obat yang dapat diresepkan untuk pasien atau dibeli oleh masyarakat untuk mencegah penimbunan, simplifikasi proses perizinan industri hingga memperbanyak tempat tidur rumah sakit.Kata Kunci: Alat kesehatan; Farmasi; COVID-19.